Some Results in Cone Metric Space, Using Semi-Compatible and Reciprocally Continuous Mappings - Perala, Chiranjeevi; Srinivas, V. (Communications in Mathematics and Applications, 2022)
In this paper, we establish a result in cone metric space by generalizing the theorem proved by Jain et al. (Compatibility and weak compatibility for four self maps in a cone metric space, Bulletin of Mathematical Analysis and Applications 2(1) (2010), 15 – 24) by employing certain weaker conditions such as semi-compatible, reciprocally continuous and sub sequentially continuous mappings. Further, our result is supported by discussing a relevant example.